2020
DOI: 10.1093/rheumatology/kez651
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in activin A–myostatin–follistatin system associate with disease activity in inflammatory myopathies

Abstract: Objectives The aim of this study was to investigate the systemic and skeletal muscle levels of atrophy-associated myokines in patients with idiopathic inflammatory myopathies (IIM) and their association with clinical characteristics of myositis. Methods A total of 94 IIM patients and 162 healthy controls were recruited. Of those, 20 IIM patients and 28 healthy controls underwent a muscle biopsy. Circulating concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 44 publications
12
19
1
Order By: Relevance
“…A similar mechanism emerges in idiopathic inflammatory myopathies. Vernerova et al, demonstrated that such disorders with decreased serum myostatin level associated with an increase of circulating follistatin concentration pose as a possible compensatory mechanism attempting to counteract muscle hypotrophy by inhibiting myostatin/ActRIIB signaling in such disorders [ 104 ]. All these novel findings greatly expand the understanding of myostatin in neuromuscular diseases and prove its viability as a biomarker in these conditions.…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%
“…A similar mechanism emerges in idiopathic inflammatory myopathies. Vernerova et al, demonstrated that such disorders with decreased serum myostatin level associated with an increase of circulating follistatin concentration pose as a possible compensatory mechanism attempting to counteract muscle hypotrophy by inhibiting myostatin/ActRIIB signaling in such disorders [ 104 ]. All these novel findings greatly expand the understanding of myostatin in neuromuscular diseases and prove its viability as a biomarker in these conditions.…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%
“…This investigation's nding of higher MSTN levels in DM patients compared to controls is in contrast to one study evaluating different myositis subtypes. Vernerova et al [9] could not reveal signi cant differences in serum levels of MSTN in their DM patients compared to healthy controls. However, comparison between these two studies is di cult because characteristics of patients are only given for the whole group of idiopathic in ammatory myopathy patients; no separate data of the included DM patients are shown.…”
Section: Resultsmentioning
confidence: 78%
“…Pathophysiological mechanisms of DM-associated muscle and bone strength loss are not well investigated in DM patients. Only one study [9] evaluated the above-mentioned regulators of muscle growth in DM patients so far. Thus, the aim of this study was to investigate the pathophysiological role of important factors regulating myogenesis and bone metabolism in patients with DM.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Follistatin gene transfer to sIBM patients-clinical trial, resulted in an improvement in muscle regeneration [117]. (iii) Follistatin high serum levels concomitant with decreased serum myostatin levels in IIM patients [118].…”
Section: Follistatinmentioning
confidence: 99%
“…Vernerova et al reported higher follistatin and lower myostatin levels in circulation and attenuated expression of myostatin pathway signaling components in skeletal muscle in IIM patients compared with healthy controls [ 118 ].…”
Section: Follistatinmentioning
confidence: 99%